Study of Making Gluten-Free Fettuccine from Taro Flour (Colocasia esculenta L. Schoot) - Rahardjo, Sekti; Aminudin,; Saleha,; Sriwulandari, Tatik; Rahmaniyah Utami, Nisa (JURNAL AGROINDUSTRI HALAL, 2024)
We often encounter fettuccine pasta in cafes and restaurants, usually made from wheat flour as the main ingredient. Wheat flour is a food ingredient that contains gluten, which is a protein compound from cereals that cause allergies and irritate the small intestine and can also cause celiac (autoimmune) disease in certain people. Several studies have substituted wheat flour for making fettuccine with non-gluten taro flour. The formula obtained is still a mixture of taro flour and wheat flour. This research used 100% pure taro flour with additional ingredients of two types of egg yolk, namely chicken egg yolk and duck egg yolk. This research aimed to determine the organoleptic results of fettuccine from 100% taro flour based on the formulation using the type of egg yolk and boiling time. This study used a completely randomized trial (CRD) design with four treatments and two repetitions. The types of treatment in this study were the use of duck eggs with a boiling time of 35 seconds, the use of boiled duck eggs for 1 minute, the use of boiled chicken eggs for 35 seconds, and the use of boiled chicken eggs for 1 minute. The research results showed that fettuccine was successfully made using 100% taro flour without being mixed with wheat, using additional egg yolk as a binder. A perfect assessment was obtained from the expert panelists for the duck egg yolk formula boiling for 1 minute. The type of egg yolk and boiling time affect the sample in terms of taste, color, and texture, but not aroma.